Comparing the utility of 30- and 60-minute cortisol levels after the standard short synacthen test to determine adrenal insufficiency: A retrospective cross-sectional study. Issue 43 (23rd October 2020) - Butt, Muhammad Imran; Alzuhayri, Nouf; Amer, Lama; Riazuddin, Muhammad; Aljamei, Hadeel; Khan, Muhammad Sohaib; Abufarhaneh, Mohammed; Alrajhi, Eman; Alnassar, Anhar; Alahmed, Reem; Aljayar, Dina Mahmoud Ahmad; Abothenain, Fayha Farraj; et al.
Abstract : Abstract: Short Synacthen test (SST) involves measuring the baseline, 30-, and 60-minute serum cortisol levels, after injecting 250 μg of synthetic adrenocorticotropic hormone or Synacthen (ACTH). This study aimed to review the current clinical practice of performing SST to establish a standardized test protocol and to additionally test the hypothesis regarding performing the 60-minute cortisol test alone and the dependence of overall SST result on baseline cortisol level. Patients >14 years who underwent SST from January 2010 to December 2017 were included. Pearson's chi-square cross-tabulation was used to identify individuals with inconsistent 30- and 60-minute serum cortisol test results. Logistic regression analysis was performed to predict normal responses based on the baseline cortisol value. Of the 965 patients identified from pharmacy, medical, and laboratory records, 849 were included. Mean baseline, 30-, and 60-minute cortisol levels after ACTH injection were 394 ± 286.58, 722 ± 327.11, and 827 ± 369.30 nmol/L, respectively. Overall, 715 (84%) and 134 (16%) patients had normal and abnormal responses, respectively. Primary and secondary adrenal insufficiency was diagnosed in 10% and 35%, respectively, while ACTH levels were not measured in 55% of the patients. Overall, 9.49% (n = 72) of the patients had a suboptimal response at 30 minutes, but reached the threshold value of 550 nmol/L at 60 minutes. This particular subgroup's mean change (240 nmol/L) in cortisol level from baseline to 30-minute was higher than that observed in patients with abnormal response at both time-points (mean change, 152 nmol/L). No patient with 30-minute optimal responses had 60-minute suboptimal responses. The baseline serum cortisol threshold of ≥226 nmol/L had 80% sensitivity, 71% specificity, and 93% positive predictive value for detecting a normal SST ( P -value < .0001). Relying on a 60-minute cortisol level can identify all normal and abnormal responses, while relying on 30-minute cortisol level alone may produce false-positives. Additionally, a baseline cortisol level of ≥226 nmol/L is a reliable threshold for determining adequate adrenal function, particularly with a low pretest hypoadrenalism probability.